Mood and Modality Analysis in the Chronicles of Mulan Movie - Jenita Anjani Sembiring; Leony Aisah Habibah (English Teaching and Linguistics Journal (ETLiJ), 2022)
The purpose of the study is to find out how a woman communicates with the environment through the expressions shown in the film. Data used is the entire utterance of a woman named Mulan. In terms of data collection, the author uses a non-participant method observation or not participating directly in study and note-taking techniques. on the data analysis method, The author uses qualitative data analysis methods. Study result shows that the woman, Mulan, is more dominant in using the sentence a statement that has a subject + finite clause structure and a middle value of the modality when he talked to father, commander, and mage. his sister. From result The study conducted can be concluded that he prefers to provide information rather than give questions or orders. Moreover, Mulan who has a strong and brave character as a woman who pretends to be a man to join the war, has the courage to argue or say something more than the people around her. While the use of a Modality shows that as a woman who goes to war, Mulan wants to show her courage in convincing her Father, Commander and Magician she faces, especially by using the median value of Modality.